1997
DOI: 10.1161/01.atv.17.11.2940
|View full text |Cite
|
Sign up to set email alerts
|

Altered Transfer of Cholesteryl Esters and Phospholipids in Plasma From Alcohol Abusers

Abstract: The net mass transfer (NMT) of cholesteryl esters (CEs), triglycerides (TGs), and phospholipids (PLs) between lipoproteins was measured after incubation of fresh plasma for up to 2 hours from 18 male alcohol abusers and 17 male volunteer control subjects. In alcohol abusers the mean value of CE NMT was 3.7 nmol.mL-1.h-1 from apolipoprotein B-containing lipoproteins (apoB-containing lipoproteins) to HDL and in control subjects 8.7 nmol.mL-1.h-1 from HDL to apoB-containing lipoproteins. The NMT of PL was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…In addition, alcohol-induced phospholipid transfer protein (PLTP) activity, which shifts PL from TG-rich lipoproteins to HDL, appears to increase HDL 2b at the expense of HDL 3a (large HDL 3 ) (37). The reduction of CETP and the increase of PLTP were confirmed by another study, which also observed an increase in the net PL transfer from apoB-containing lipoproteins to HDL in alcoholics (38). However, none of these enzymes seems to be changed in moderate alcohol consumers (39)(40)(41).…”
Section: Discussionmentioning
confidence: 65%
“…In addition, alcohol-induced phospholipid transfer protein (PLTP) activity, which shifts PL from TG-rich lipoproteins to HDL, appears to increase HDL 2b at the expense of HDL 3a (large HDL 3 ) (37). The reduction of CETP and the increase of PLTP were confirmed by another study, which also observed an increase in the net PL transfer from apoB-containing lipoproteins to HDL in alcoholics (38). However, none of these enzymes seems to be changed in moderate alcohol consumers (39)(40)(41).…”
Section: Discussionmentioning
confidence: 65%
“…An increase in NEFA is also a characteristic of other conditions associated with an increase in PLTP. PLTP activity is elevated in alcoholics, who demonstrate increased NEFA concentrations, and PLTP decreases upon withdrawal (33,34). PLTP activity decreases with the administration of Acipimox, which is thought to inhibit hormone-sensitive lipase and thus decrease NEFA release from adipose tissue (35).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on an extensive set of UCF-based lipoprotein data in which the apoB particles were isolated as VLDL, IDL, and LDL fractions and the HDL particles separated to HDL 2 and HDL 3 (18)(19)(20). The use of UCF is tedious and expensive and thus, most often only the total HDL fraction is physically isolated and the IDL fraction might not be separately spun.…”
Section: Lipoprotein Datamentioning
confidence: 99%
“…However, the molecular composition as well as the metabolic and structural interrelationships between lipoprotein particles are often hampered due to limited measurement data available and the molecular complexity of lipoprotein metabolism. Physical isolation of lipoproteins by sequential ultracentrifugation (UCF) is common to measure plasma lipoprotein concentrations ( 17 ) but most studies are restricted regarding the analyzed subpopulations and detailed attention is rarely paid to the molecular composition of the isolated particles.Here, we focus on an extensive set of UCF-based lipoprotein data in which the apoB particles were isolated as VLDL, IDL, and LDL fractions and the HDL particles separated to HDL 2 and HDL 3 (18)(19)(20). The use of UCF is tedious and expensive and thus, most often only the total HDL fraction is physically isolated and the IDL fraction might not be separately spun.…”
mentioning
confidence: 99%